Pengaruh Perceived Organizational Support terhadap Work Engagement pada Guru SLB - Shofy Chaerunnisa Zahara; Yuli Aslamawati (Bandung Conference Series: Psychology Science, 2024)
Abstract. The lack of special school teachers is a problem because they will experience an increase in workload. This increase in workload will affect teacher performance so that it requires an engaged condition to improve teacher performance. Work engagement is a positive psychological construct in which employees feel enthusiastic at work. Perceived organizational support according to Eisenberger et al., (1986) is the employee's perception of the extent to which the organization appreciates their contribution during work and cares about their welfare. This study aims to determine how much influence perceived organizational support has on work engagement in special education teachers in Cirebon Regency. The method used in this research is quantitative method. The subjects in this study were 87 special school teachers in Cirebon Regency. The data analysis technique used is simple linear regression. The measuring instrument used in this study is SPOS (Survey Perceived Organizational Support) which refers to the theory of Eisenberger et al. (1986) and adapted by Kurniawan and Harsono (2021) and the UWES (Utrecht Work Engagement Scale) measuring instrument adapted by Kristiana et al. (2018). The results of this study indicate that Perceived Organizational Support only has an effect of 6.5% on Work Engagement. Abstrak. Kurangnya jumlah guru sekolah luar biasa menjadi sebuah masalah karena akan mengalami peningkatan beban kerja. Peningkatan beban kerja ini nantinya akan mempengaruhi kinerja guru sehingga membutuhkan kondisi yang engaged untuk meningkatkan kinerja guru. Work engangement merupakan konstruks psikologi positif yang dimana para karyawan merasa antusias dalam bekerja. Perceived organizational support menurut Eisenberger et al., (1986) merupakan persepsi karyawan mengenai sejauh mana organisasi menghargai kontribusi mereka selama bekerja dan peduli akan kesejahteraan mereka. Penelitian ini bertujuan untuk mengetahui seberapa besar pengaruh perceived organizational support terhadap work engagement pada guru SLB di Kabupaten Cirebon. Metode yang digunakan pada penelitian ini adalah metode kuantitatif. Subjek pada penelitian ini adalah guru sekolah luar biasa di Kabupaten Cirebon sebanyak 87 orang. Teknik analisis data yang digunakan adalah regresi linier sederhana. Alat ukur yang digunakan dalam penelitian ini adalah SPOS (Survey Perceived Organizational Support) yang mengacu pada teori Eisenberger et al. (1986) dan diadaptasi oleh Kurniawan dan Harsono (2021) dan alat ukur UWES (Utrecht Work Engagement Scale) yang diadaptasi oleh Kristiana et al. (2018). Hasil penilitian ini menunjukkan bahwa Perceived Organizational Support hanya memberikan pengaruh sebesar 6,5% terhadap Work Engagement.